Micro-credit programmes of different NGOs/MFIs: A comparative study (Journal of the Bangladesh Agricultural University, 2013)
This study evaluated micro-credit programmes of six leading NGOs/MFIs (BRAC, Grameen Bank, PROSHIKA, ASA, SSS and TMSS) in terms of the clients views towards the programmes. The objective of this project is to develop a selection criterion to identify the efficient programme. A total of 406 members from the selected NGOs/MFIs operating micro-credit programmes in Dhaka, Mymensingh, Sherpur, Netrokona, Kishoreganj, Norshingdi, Sylhet and Lalmonirhat were interviewed. The data analyses reveal that the majority of the large amount of loans (above Tk.15000) was taken by GB members (33.7 percent). The respondents who knew the actual interest rate were more in BRAC (42.9 percent). Workers of GB ranked first in terms of field visit (24.9 percent). Request needed to get loan was the highest in BRAC (53.0 percent). The satisfaction level of respondents was more in GB and low in SSS. Poverty alleviation due to micro-credit was the highest among GB members (22.0 percent). Logistic regression analysis suggests that amount of loan taken, experience of poverty alleviation and NGO membership are three important determinants of satisfaction level on the micro-credit programme. A set of characteristics were chosen to find out the best performing micro-credit operating NGOs/MFIs. The data analysis suggests that TMSS is the best performing NGOs/MFIs. The successive NGOs/MFIs in order of rank are GB, SSS, PROSHIKA, BRAC and ASA, respectively.DOI: http://dx.doi.org/10.3329/jbau.v10i2.14922 J. Bangladesh Agril. Univ. 10(2): 297-302, 2012